Exploring Political Trust: A Bibliometric Study on the Evolution and Perspectives in Political Psychology - Faradila Umaiya; Novi Qonitatin (Green Publisher, 2025)
Political trust is defined as the support of citizens for political institutions, reflecting their confidence in the actions and policies of the government. This study aims to examine the research trends on political trust, particularly in the field of psychology. The research method used is bibliometric analysis with SCOPUS database, using